Brain and cord imaging features in neuromyelitis optica spectrum disorders. Issue 3 (28th January 2019) - Cacciaguerra, Laura; Meani, Alessandro; Mesaros, Sarlota; Radaelli, Marta; Palace, Jacqueline; Dujmovic‐Basuroski, Irena; Pagani, Elisabetta; Martinelli, Vittorio; Matthews, Lucy; Drulovic, Jelena; Leite, Maria Isabel; Comi, Giancarlo; et al.
Abstract : Objectives: To validate imaging features able to discriminate neuromyelitis optica spectrum disorders from multiple sclerosis with conventional magnetic resonance imaging (MRI). Methods: In this cross‐sectional study, brain and spinal cord scans were evaluated from 116 neuromyelitis optica spectrum disorder patients (98 seropositive and 18 seronegative) in chronic disease phase and 65 age‐, sex‐, and disease duration–matched multiple sclerosis patients. To identify independent predictors of neuromyelitis optica diagnosis, after assessing the prevalence of typical/atypical findings, the original cohort was 2:1 randomized in a training sample (where a multivariate logistic regression analysis was run) and a validation sample (where the performance of the selected variables was tested and validated). Results: Typical brain lesions occurred in 50.9% of neuromyelitis optica patients (18.1% brainstem periventricular/periaqueductal, 32.7% periependymal along lateral ventricles, 3.4% large hemispheric, 6.0% diencephalic, 4.3% corticospinal tract), 72.2% had spinal cord lesions (46.3% long transverse myelitis, 36.1% short transverse myelitis), 37.1% satisfied 2010 McDonald criteria, and none had cortical lesions. Fulfillment of at least 2 of 5 of absence of juxtacortical/cortical lesions, absence of periventricular lesions, absence of Dawson fingers, presence of long transverse myelitis, and presence of periependymal lesions along lateral ventricles discriminated neuromyelitis optica patients in both training (sensitivity = 0.92, 95% confidence interval [CI] = 0.84–0.97; specificity = 0.91, 95% CI = 0.78–0.97) and validation samples (sensitivity = 0.82, 95% CI = 0.66–0.92; specificity = 0.91, 95% CI = 0.71–0.99). MRI findings and criteria performance were similar irrespective of serostatus. Interpretation: Although up to 50% of neuromyelitis optica patients have no typical lesions and a relatively high percentage of them satisfy multiple sclerosis criteria, several easily applicable imaging features can help to distinguish neuromyelitis optica from multiple sclerosis. ANN NEUROL 2019;85:371–384.